Walt Whitman Among the French : Poet and Myth. - Erkkila, Betsy (Princeton : Princeton University Press, 2014)
As the first full treatment of Walt Whitman's French sources and his later impact on French writers, this book revises our image of the poet and challenges many critical assumptions. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is t.
Cover; Introduction; 1. France in Whitman; I. The French Background; 2. Whitman and French Symbolism; 3. Whitman and Post-Symbolism; B. André Spire and Charles Péguy; 4. Whitman and L'esprit Nouveau; Appendix I. Chronological List of French Criticism of Whitman Since 1861; Appendix II. Chronological List of French Translations of Whitman Since 1886; Notes.
Print version record.
eBooks on EBSCOhost
Keywords: Whitman, Walt, -- 1819-1892 -- Influence; Whitman, Walt, -- 1819-1892 -- Sources; Whitman, Walt, -- 1819-1892 -- Sources; Whitman, Walt, -- 1819-1892 -- Influence; Whitman, Walt, -- 1819-1892; French literature -- 20th century -- History and criticism; French literature -- 19th century -- History and criticism; Symbolism (Literary movement) -- France; Symbolisme (Mouvement littéraire) -- France; Littérature française -- 20e siècle -- Histoire et critique; Littérature française -- 19e siècle -- Histoire et critique; LITERARY CRITICISM -- Poetry; POETRY -- General; French literature; Influence (Literary, artistic, etc.); Symbolism (Literary movement); France; 1800-1999; Criticism, interpretation, etc; Sources